SAT0259 Patient Reported Outcomes and Quality of Life in a Cohort of Patients Affected by Entheropathic Spondyloarthritis: Preliminary Results from a Monocentric Prospective Observational Study. (9th June 2015) - Luchetti, M.M.; Balloni, A.; Benfaremo, D.; Bolognini, L.; Farinelli, A.; Cedraro, S.; Rossini, M.; Capeci, W.; Manfredi, L.; Postacchini, L.; Tedesco, S.; Fava, G.; et al.
Abstract : Background: Enteropathic spondyloarthritis (ES) belongs to spondyloarthritis (SpA) and are the most frequent extra-intestinal manifestation in patients with inflammatory bowel diseases (IBD). The coexistence of gut and articular inflammation advocates an integrated approach for the clinical management of these patients in clinical practice (1). Objectives: We carried out a clinical study, henceforth defined SPIB (SP ondyloarthritis in I nflammatory B owel disease), in the outpatient clinics and in the clinical ward of the gastroenterology and internal medicine departments, having the following end-points; a) the early diagnosis of ES; b) the evaluation of the quality of life before and after therapeutic integrated approach. Methods: From January, 2014 to January 2015, 198 consecutive IBD pts were screened; 48 refused to participate to the study and 154 were evaluated at baseline and after 3 and 6 months for gastrointestinal symptoms and activity, patient-reported outcomes of the quality of life, and rheumatologic symptoms (Fig.1 ). After a gastroenterologist and rheumatologist evaluation, the therapeutic strategy was chosen in concert based on gastrointestinal and joint disease activity, and the presence of peripheral and/or axial involvement of the joints. Results: 65 (33, 6%) of the 154 pts complained of articular symptoms and in 51 of 65 (25, 8% of all IBD pts) an active enteropathic SpA (ES) was diagnosed. Peripheral arthritis was present in 23 pts (45%) and axial involvement in 28 pts (55%). Articular symptoms had been present for 5±4, 9 yrs in 51% of the ES pts. The quality of life in the cohort of ES pts, compared to that of IBD pts, was significantly worsened by articular symptoms (Fig.1A ). 20 ES pts were treated with metotrexate, 2 with salazopyrine, 5 with infliximab, and 23 with adalimumab. After 6 months of treatment, 90% of the ES pts reported a significant improvement in their quality of life (Fig.1B ). A significant improvement of both gastrointestinal (Fig. 1B ) and articular disease (Fig.1C ) was achieved in 88% of the patients, mostly in pts receiving anti-TNF-alfa drugs. Conclusions: The early diagnosis of enteropathic spondyloarthritis and the choice of the optimal therapeutic strategy constitute a major topic in clinical practice (1). Our study confirmed the importance of an integrated clinical evaluation of ES pts carried out by the gastroenterologist and rheumatologist, for a correct diagnosis and the choice of the optimal therapeutic strategy. References: Olivieri I. et al. Autoimmun Rev 2014, 8:822-30. Disclosure of Interest: None declared